Utilizing Recycled Evaporated Organic Solvent Waste for Green Chemistry in Chemical Laboratories to Reduce Liquid Waste - Rachmawati, Rachmawati; Wati, Idah Dianah (Proceeding Series of International Conference on Arts and Humanities, 2022)
The use of solvents, especially organic solvents in chemical laboratories, particularly in extraction processes, cannot be separated from laboratory activities. Since extracted organic solvents are not seen as having desirable qualities, they are not recycled and end up as liquid waste. The evaporation method was used to handle organic solvent waste from evaporation, and the evaporator exhibited the same physical and chemical characteristics as technical solvents. This study aimed to determine whether organic solvent waste from the evaporation process could be recycled and reused following the concept of green chemistry in laboratory waste treatment. The research method used in processing the recycled organic solvent waste (ethanol & methanol) from the evaporation was the experimental method through the evaporation process by evaporation and characterized based on the FT-IR and GC-MS test parameters on organic solvents pro-analysis and technical. Based on the results, the correlation coefficient analysis for testing the second recycled methanol- pro-analysis methanol, the second recycled methanol - technical methanol, and the second recycled ethanol- pro-analysis ethanol was quite strong. according to the results of the solvent characterization test of methanol and ethanol from the second recycling solvents by evaporation through the FT-IR test. Technical correlation values of 0.9982, 0.9983 and 0.9902. Meanwhile, the second recycled ethanol- pro-analysis ethanol had correlation coefficient value, 0.0079, was quite low. However, the second recycled solvent did not significantly differ from the technical solvent in the GC-MS test (p>0.05).